Improving Heat Resistance of Nile Tilapia (Oreochromis niloticus) by Dietary Zinc Supplementation. (18th March 2022) - Yang, Yuanting; Wu, Zhiqian; Ren, Yanli; Zhou, Zhiqing; Wang, Wen-Xiong; Huang, Yunmao; Shu, Xugang
Abstract : In this study, we investigated the effects of zinc threonine supplementation on growth, immunity-related genes, antioxidative stress, and resistance to heat stress (HS) in Nile tilapia. A total of 300 Nile tilapia (76.69 ± 0.11 g) were randomly allocated into five zinc treatments, with three replicates of 20 fish in each treatment. Based on the control group with zinc-free feeds, dietary zinc levels of 20 or 40 mg/kg diet were added in the form of zinc sulfate (ZnSO4 ) and zinc threonine (Thr-Zn). After 45 days of feeding, part of the fish was exposed to HS. The highest performance of growth and feed intake was found in fish fed with zinc (ZnSO4 or Thr-Zn) at 40 mg/kg, which also significantly elevated the villus length and absorption area. Additionally, significantly higher values of superoxide dismutase, catalase, and glutathione peroxidase activity but lower value of malondialdehyde both before and after the heat stress were documented in fish fed with zinc at 40 mg/kg in diets. After HS, dietary supplementation with zinc threonine significantly reduced the expression of HSP 70 in the liver but increased the expression of IL-10 and TNF- α . Our study demonstrated that zinc threonine supplementation at 40 mg/kg facilitated the coping of tilapia with HS by improving the growth, intestinal morphology, antioxidative resistance, and immune responses.